2020
DOI: 10.34208/jba.v22i1.747
|View full text |Cite
|
Sign up to set email alerts
|

Can Audit Committee Reduce Real Earnings Management?

Abstract: The objective of research was to give empirial evidence the influence of audit committee and directors on real earnings management (REM). The samples of this research consist of 336 data from 84 public manufacturing companies from 2013 until 2016 and selected by purposive sampling method. The result showed that the audit committee expertise and independence directors have significantly and postive influence on REM. The board of directors have significantly and negative influence on REM. The influence of audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
0
11
1
Order By: Relevance
“…Many or at least the number of boards of directors is not a determining factor for the occurrence of real earnings management because the decision to do earnings management is more driven by situations, conditions such as pressures or certain opportunities, not by the number of boards of directors owned by the company. The findings do not support previous research by Susanto & Pradipta (2020), which showed that a larger board of directors could reduce real earnings management actions because more and more parties supervise and have good information about the company.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Many or at least the number of boards of directors is not a determining factor for the occurrence of real earnings management because the decision to do earnings management is more driven by situations, conditions such as pressures or certain opportunities, not by the number of boards of directors owned by the company. The findings do not support previous research by Susanto & Pradipta (2020), which showed that a larger board of directors could reduce real earnings management actions because more and more parties supervise and have good information about the company.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on its role in the company, it is expected that more and more members of the board of directors will minimize the rate of earnings manipulation (Yunietha & Palupi, 2017). However, previous research results by Shahwan & Almubaydeen (2020), Abbasi & Qomi (2017); Susanto & Pradipta, 2016;Susanto & Pradipta (2020) shows that the board of directors has a negative effect on real earnings management. The board of directors is an internal party responsible for the company's operations, so it maximizes the company's welfare.…”
Section: Board Of Directors Size and Real Earnings Managementmentioning
confidence: 90%
See 1 more Smart Citation
“…However, different attributes of the audit committee contribute to determining earnings management behaviour. To make it easier for companies to see an effective financial reporting system, it is better for companies to have an audit committee that has experience or expertise in finance and accounting (Susanto & Pradipta, 2020). Of the total members of the audit committee, there should be at least one member who can be in the field of accounting or finance and the chairman of the audit committee can at least read and understand the financial statements.…”
Section: Real Earnings Managementmentioning
confidence: 99%
“…However, studies that are more recent provide evidence that strong AC financial expertise may inadvertently encourage managers to increase REM. For example, Susanto and Pradipta (2020) suggest that ACs, which have strong financial expertise, may pressure managers to engage in REM. They used 336 observations from 84 public manufacturing companies from 2013 to 2016 and note that AC financial expertise is positively associated with REM.…”
Section: Ac Financial Expertise Aem and Remmentioning
confidence: 99%